Laminated Glass Cantilevered Plates under Static and Impact Loading - Luigi Biolzi; Antonio Bonati; Sara Cattaneo (Advances in Civil Engineering)
The structural performance of cantilevered laminated glass plates for different glass thicknesses and interlayers is considered in this paper. Heat-strengthened and tempered glass plies and two different interlayer films were utilized. The response of laminated glass specimens is then evaluated under low-velocity hard and semirigid impacts. Experimental findings were simulated and discussed by means of finite element analyses. In particular, this discussion includes the evaluation of the influence that the fixed edge clamping technique (number of clamps, their size, and their stiffness) has on the stress distribution in the specimens.